Fenomena Live Streaming Shopping guna Meningkatkan Impulsive Buying Intention dalam E-commerce: Kajian SOR - Ratna Enjelina; Yolanda Masnita (CV. Ulil Albab Corp, 2024)
Live streaming shopping is an interactive online shopping method where sellers or streamer broadcast videos in real time to market innovative products. This study aims to analyze factors that can influence impulsive buying intentions in live streaming shopping using the Theory of Stimulus-Organism-Response. The study used a population of users who have watched live streaming shopping on e-commerce. The total sample in this study was 140 respondents, collected using purposive sampling. Data processed using Smart PLS version 4.0. The results obtained in this study are that convenience and arousal have a positive effect on perceived enjoyment, and perceived enjoyment has a positive impact on impulsive buying intention. Demand and interactivity have no influence on impulsive buying intentions. These findings help develop more effective marketing strategies and understand the changing consumer trends. ive streaming shopping is an interactive online shopping method where sellers or streamers broadcast videos in real-time to market innovative products. This research aims to analyze factors that can influence impulsive buying intention in live streaming shopping using the Stimulus-Organism-Response (SOR) theory. This research uses a population, namely users who have watched live streaming shopping on e-commerce. The number of samples in this study was 140 respondents who were collected using the purposive sampling method. Data is processed using Smart PLS version 4.0. The results obtained in this research are that convenience and arousal have a positive effect on perceived enjoyment and perceived enjoyment has a positive effect on impulsive buying intention. Demand and interactivity have no effect on impulsive buying intention. These findings help businesses develop more effective marketing strategies and understand changing consumer trends.